PENGARUH FAKTOR PENDIDIKAN, MOTIVASI PETANI, TEKNOLOGI SERTA SARANA PRASARANA TERHADAP KINERJA PENYULUHAN PERTANIAN - Tambunan, Herlina Yolanda; Nainggolan, Mai Fernando (Jurnal Agriust, 2026)
This study aims to examine the influence of educational factors of extension workers, farmers’ motivation, technology, and facilities/infrastructure on the performance of agricultural extension in Sabungan Nihuta II Village, Sipahutar District, North Tapanuli Regency. This research uses a quantitative approach with a multiple linear regression method. The population consists of 360 farmers and extension workers, with 189 respondents selected using Slovin’s formula and simple random sampling. Data were collected through a Likert scale questionnaire (1–5) and analyzed using SPSS. The results indicate that simultaneously, education, farmers’ motivation, technology, and facilities/infrastructure significantly affect agricultural extension performance (F-count = 50.846; p = 0.000). Partially, farmers’ motivation has the most dominant effect, followed by facilities/infrastructure, education, and technology. The coefficient of determination (R² = 0.725) shows that 72.5% of the variation in extension performance can be explained by these four variables. This study highlights the importance of improving the education of extension workers, farmers’ motivation, technology utilization, and facility support to enhance the effectiveness of agricultural extension.